The sella turcica: a brief review of the morphology analysis in dental research - Jordanna de Melo Teixeira do Brasil; Erika Calvano Küchler; PatríciaValéria Manozzo Kunz; César Penazzo Lepri; Vinícius Rangel Geraldo Martins; Isabela Ribeiro Madalena; Camila Paiva Perin; Natanael Henrique Ribeiro Mattos; Juliana Pierdoná de Castro; Fernando Carlos Hueb de Menezes; et al. (Revista Sul-Brasileira de Odontologia, 2022)
Sella turcica is an intracranial bone depression located in the sphenoid bone that houses the pituitary gland, which is an important gland in the secretion of various hormones. Literature review: Variations in the morphology of the sella turcica can alter the morphology of the pituitary, which can lead to changes in hormone secretion and dental anomalies. There are studies that evaluate the sella turcica using metric methods and other studies that evaluate them with non-metric methods. Researchers use lateral radiographs and/or computed tomography to visualize the sella turcica. The purpose of this brief review was to revise the methods used to study sella turcica morphology in dental research. The literature search for sella turcica morphology was carried out with the following key words (sella turcica, bridging of sella, size, shape of sella turcica and sella turcica morphology) and using the search engines (Pubmed and Google scholar). According to the research, three methods of analyzing the sella turcica were observed, according to the measurements (length, width, diameter, area, depht, sella height posterior, sella height anterior), degree of calcification (class I / type I / group I, class II / type II / group II, class III / type III / group III) and format (normal sella turcica, sella turcica bridge type A – ribbon-like fusion, sella turcica bridge type B – extension of the clinoid processes, incomplete bridge, hypertrophic posterior clinoid process, hypotrophic posterior clinoid process, irregularity in the posterior part of the sella turcica, pyramidal shape of the dorsum sella, double contour of the floor, oblique anterior wall, oblique contour of the floor) of the sella turcica. Conclusion: It is expected that the three methods exposed in this review will help dental researchers to analyze sella turcica.